2022
DOI: 10.1111/apt.16965
|View full text |Cite
|
Sign up to set email alerts
|

The impact of red blood cell transfusion practices on inpatient mortality in variceal and non‐variceal gastrointestinal bleeding patients: a 20‐year US nationwide retrospective analysis

Abstract: Summary Background Previous studies in upper gastrointestinal (GI) bleeding have reported inconsistent outcomes about packed red blood cell (PRBC) transfusion practices. Aim To assess whether PRBC transfusion is more likely to be dangerous in variceal bleeding than in non‐variceal bleeding due to concern of over‐transfusion leading to elevated portal pressure. Methods We used the Nationwide Inpatient Sample (1999–2018). We identified patients with upper GI bleeding using an algorithmic approach, categorising b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(65 reference statements)
3
7
0
Order By: Relevance
“…
We thank Drs Orpen-Palmer and Stanley for their thoughtful comments about our work on the impact of red blood cell transfusion on inpatient mortality in variceal and non-variceal upper GI bleeding. 1,2 We agree with the conclusion that clinical judgement is critical in the use of red blood cell transfusion in patients with upper GI bleeding. However, we were somewhat surprised that the effect was limited mainly to variceal upper GI bleedingalthough careful analysis of the available literature aligns with this conclusion.
…”
supporting
confidence: 74%
See 1 more Smart Citation
“…
We thank Drs Orpen-Palmer and Stanley for their thoughtful comments about our work on the impact of red blood cell transfusion on inpatient mortality in variceal and non-variceal upper GI bleeding. 1,2 We agree with the conclusion that clinical judgement is critical in the use of red blood cell transfusion in patients with upper GI bleeding. However, we were somewhat surprised that the effect was limited mainly to variceal upper GI bleedingalthough careful analysis of the available literature aligns with this conclusion.
…”
supporting
confidence: 74%
“…We thank Drs Orpen‐Palmer and Stanley for their thoughtful comments about our work on the impact of red blood cell transfusion on inpatient mortality in variceal and non‐variceal upper GI bleeding 1,2 . We agree with the conclusion that clinical judgement is critical in the use of red blood cell transfusion in patients with upper GI bleeding.…”
supporting
confidence: 56%
“…Radadiya et al have undertaken a cohort study from a database of over 1000 hospitals across the United States over a 20-year period. 6 They included 10,228,54 patients with UGIB of whom 755,135 had a variceal bleed. Following a peak in 2011, the authors found a gradual reduction in the use of PRBC for UGIB.…”
mentioning
confidence: 99%
“…Variceal bleeding is very common in this group of patients and is one of the main drivers of ESLD-associated allogeneic blood transfusions [ 30 ]. Recently it has been demonstrated that allogeneic RBC transfusions are associated with higher mortality in patients with variceal bleeding compared to other bleeding patients [ 31 ]. In addition to pharmacological interventions that influence portal perfusion pressure, such as terlipressin, somatostatin, or octreotide, coagulation factors have a major role in the treatment of variceal bleeding.…”
Section: Pathophysiology Of Deranged Hemostasis In End-stage Liver Di...mentioning
confidence: 99%